Remarks on the population of the silver hake (merluccius hubbsi marini, 1933) from the area to the north and east of Falkland islands - Maxim, C.; Dumitrescu, V. (Cercetări Marine - Recherches Marines, 2026)
This work aims to present the dimension structure by classes, degree of maturation and sexes of the silver hake caught in the area to the North and East of Falkland Islands in May 1978.